Re-examination of the Natural History of High-grade T1 Bladder Cancer using a Large Contemporary Cohort - Canter,Daniel J. (2014)
IntroductionHigh-grade T1 (HGT1) bladder cancer represents a clinical challenge in that the urologist must balance the risk of disease progression against the morbidity and potential mortality of early radical cystectomy and urinary diversion. Using two non-muscle invasive bladder cancer (NMIBC) databases, we re-examined the rate of progression of HG T1 bladder cancer in our bladder cancer populations.Materials and MethodsWe queried the NMIBC databases that have been established independently at the Atlanta Veterans Affairs Medical Center (AVAMC) and the University of Pennsylvania to identify patients initially diagnosed with HGT1 bladder cancer. Demographic, clinical, and pathologic variables were examined as well as rates of recurrence and progression.ResultsA total of 222 patients were identified; 198 (89.1%) and 199 (89.6%) of whom were male and non-African American, respectively. Mean patient age was 66.5 years. 191 (86.0%) of the patients presented with isolated HG T1 disease while 31 (14.0%) patients presented with HGT1 disease and CIS. Induction BCG was utilized in 175 (78.8%) patients. Recurrence occurred in 112 (50.5%) patients with progression occurring in only 19 (8.6%) patients. At a mean follow-up of 51 months, overall survival was 76.6%. Fifty two patients died, of whom only 13 (25%) patient deaths were bladder cancer related.ConclusionsIn our large cohort of patients, we found that the risk of progression at approximately four years was only 8.6%. While limited by its retrospective nature, this study could potentially serve as a starting point in re-examining the treatment algorithm for patients with HG T1 bladder cancer.